Whole vs. Half Tablets – A Case with Diazepam Tablets - Bubić Pajić, Nataša; Račić, Anđelka; Gatarić, Biljana (Scripta Medica, 2019)
Background: Tablet splitting is commonly used in clinical practice as a way to attain a desired drug dose and/or reducing its side effects, particularly among paediatricians and psychiatrists. However, uneven tablet scoring can lead to significant fluctuations of the administered doses, where subpotency or superpotency of drugs might harm the patients. The aim of this study was to evaluate the influence of tablet splitting on dose uniformity of diazepam by the utilization of Ph. Eur. 9.0 and FDA recommendations. Methods: Mass variation of whole and half tablets in parallel with the determination of their content uniformity were determined according to the pharmacopoeial methods. The weight loss after tablet splitting was assessed by employing FDA guidelines. We also investigated if tablet splitting influenced in vitro dissolution properties of diazepam tablets. Results: Diazepam whole tablets fulfilled the pharmacopoeial requirements in regard to the all investigated properties. The weight uniformity of scored diazepam tablets ranged from 63.80% to 122.55% label claim. The losses of mass after splitting diazepam tablets were 5.71%. Despite the average content of diazepam in half tablets was found to be 104.24% label claim, the requirements of Ph. Eur. were not fulfilled. Diazepam content in half tablets ranged from 0.76 mg to 1.21 mg, thus, patients might receive doses that varied by as much as 45%. However, after weight adjustment, diazepam content in each of the tested half tablets in the range of 85-115% of the average drug content meeting the Ph. Eur. criteria. Dissolution profiles of whole and half tablets were found to be similar, following Hixson-Crowell kinetic model. Conclusion: According to the results, splitting of diazepam tablets greatly influenced the drug content in the obtained parts, i.e. the dose accuracy was fully dependent of the ability to score the tablet into exactly equal halves. Key words: tablet splitting, diazepam, tablet scoring, half tablets, dose adjustment